Penerapan Metode ROC dan Weighted Aggregated Sum Product Assesment (WASPAS) dalam Penerimaan Asisten Perkebunan - Rakhmi Khalida; Budianto Bangun; Mesran Mesran; Nona Oktari (STMIK Budi Darma, 2021)
A plantation assistant is a person who is responsible for managing a plantation, in the selection of plantation assistants there are still obstacles in the selection, this is because many applicants enter and the assessment is still subjective. To overcome this problem, in this study, the author uses the Weighted Aggregated Sum Product Assessment (WSPAS) method to determine the acceptance of Plantation Assistants. The WASPAS method is considered in accordance with the selection of plantation assistants, because the WASPAS method will perform a ranking process based on attributes with different weights so that the results become more optimal. For maximum results, the author uses weighting by applying the Rank Order Centroid (ROC) method. The results of the study provide recommendations for the 8th alternative which has the highest value with a value of 0.970 to become a Plantation Assistant.